Bad Boys Talking: Using the Views of ‘Disruptive’ Children to Improve the Way We Teach - Garner, Philip (REACH: Journal of Inclusive Education in Ireland, 1995)
A research project carried out in the north-west of England examined the views of pupils, judged by teachers as disruptive, on a range of issues including teacher characteristics, curriculum relevance, inappropriate behaviour and the ethos and organisation of the school. Much of what children say about their lives in school can be used to promote more effective teaching, to inform professional development sessions at whole school meetings and to empower pupils in their own learning.